2020
DOI: 10.3168/jds.2019-17971
|View full text |Cite
|
Sign up to set email alerts
|

Genetic correlations of milk fatty acid contents predicted from milk mid-infrared spectra in New Zealand dairy cattle

Abstract: The objective of this study was to estimate genetic correlations among milk fatty acid (FA) concentrations in New Zealand dairy cattle. Concentrations of each of the most common FA, expressed as a percentage of the total FA, were determined by gas chromatography on a specific cohort of animals. Using this data set, prediction equations were derived using mid-infrared (MIR) spectroscopy data collected from the same samples. These prediction equations were applied to a large data set of MIR measurements in 34,14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 38 publications
(80 reference statements)
5
14
0
Order By: Relevance
“…Although low, such correlations were not null as standard errors of estimates were ≤0.01. Overall, weak correlations of SCS with FA were observed also by Lopez-Villalobos et al [9], except for moderate negative associations with C4:0 (−0.25), C6:0 (−0.21) and SCFA (−0.26). Genetic correlations between SCS and FA were estimated also by Petrini et al [30], who reported weak negative correlations with SFA, C16:0 and C18:0, and weak positive correlations with UFA, MUFA, PUFA, and C18:1.…”
Section: Genetic and Phenotypic Correlations Between Fatty Acids And supporting
confidence: 58%
See 4 more Smart Citations
“…Although low, such correlations were not null as standard errors of estimates were ≤0.01. Overall, weak correlations of SCS with FA were observed also by Lopez-Villalobos et al [9], except for moderate negative associations with C4:0 (−0.25), C6:0 (−0.21) and SCFA (−0.26). Genetic correlations between SCS and FA were estimated also by Petrini et al [30], who reported weak negative correlations with SFA, C16:0 and C18:0, and weak positive correlations with UFA, MUFA, PUFA, and C18:1.…”
Section: Genetic and Phenotypic Correlations Between Fatty Acids And supporting
confidence: 58%
“…Nevertheless, those authors [6] reported approximate genetic correlations among traits as correlations among daily breeding values, possibly without fully representing the genetic relationships between traits. Although positive genetic correlations between SFA, MUFA, and PUFA have been reported in literature [19,26], some authors [9,27,28] reported strong negative genetic correlations. As explained by Lopez-Villalobos et al [9], this discrepancy is due to the different expression of concentration of FA: as grams per 100 g of milk (positive correlation) or grams per 100 g of total FA (negative correlation).…”
Section: Genetic and Phenotypic Correlations Among Famentioning
confidence: 95%
See 3 more Smart Citations